Cohort analysis of high-risk HPV infection in adult women in Dapeng New District, Shenzhen, Guangdong Province, China - Wei, Weifeng; Zhang, Mi; Lin, Yiyuan; Li, Ziyin; Luo, Wenbo; Zhao, Weihua; Zhuang, Jing; Zhao, Weining; Xu, Zhixue; Li, Gaomin; Zeng, Wenjing; Huang, Liping; et al. (Frontiers in Microbiology, 2025)
IntroductionCervical cancer is the fourth most commonly diagnosed malignancy among women globally, with HPV infection being the primary cause. Large-scale HPV screening is crucial for early detection, as appropriate intervention in HPV-positive individuals can significantly reduce cervical cancer incidence and mortality.MethodsData were extracted from the Shenzhen Maternal and Child Health Management Information System, covering 18,667 HPV infection and cervical cancer screening instances among 15,850 women from January 1, 2020, to December 31, 2023. HPV prevalence and corresponding 95% confidence intervals (CIs) were calculated using SPSS (version 27.0).ResultsFrom January 2020 to December 2023, the overall HPV infection rate was 12.39%, with a notably higher rate of 23.38% in women over 60 years. The hr-HPV infection rate was 12.99%, with HPV types 52, 58, 16, 51, and 68 being the most common. Among women with positive ThinPrep Cytologic Test (TCT) results, the hr-HPV infection rate was 53.37%. In women with positive cervical histopathology, the hr-HPV infection rate reached 95.95%. With increased HPV vaccination doses, the infection rates of HPV16, 18, 52, 58, 51, 31, 33, 45, 6, and 11 decreased among individuals under 30, but increased in those over 45.DiscussionThese findings suggest that enhancing HPV vaccination coverage and cervical cancer screening, especially for women over 45, are effective strategies to reduce hr-HPV infection rates and cervical cancer incidence in this region.